1999
DOI: 10.1016/s0020-7292(99)00178-2
|View full text |Cite
|
Sign up to set email alerts
|

Screening for cervical neoplasia during pregnancy

Abstract: As a result of cytology's rather low yield and the small measure of agreement between the tests, cytology should be supplemented by an additional screening test in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Cronjé et al [29] observed a lower J of 0.01 between cervicography and cytology among a population of 842 women attending an antenatal clinic. The low agreement was attributed to the enlargement of the cervix during pregnancy and to excessive mucus on the surface, hampering visualization of the cervix and quality of the cervical smear.…”
Section: Discussionmentioning
confidence: 98%
“…Cronjé et al [29] observed a lower J of 0.01 between cervicography and cytology among a population of 842 women attending an antenatal clinic. The low agreement was attributed to the enlargement of the cervix during pregnancy and to excessive mucus on the surface, hampering visualization of the cervix and quality of the cervical smear.…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, elevated progesterone levels are associated with the presence of thick, sperm‐impenetrable mucus with significantly increased viscosity as compared to the follicular phase. Studies on the relationship between cytology and cervical mucus have shown that thickened mucus during pregnancy results in a decrease in the production of endocervical cells 13,14 . Accordingly, swabbing excess mucus from the cervix before scraping is known to result in a more interpretable specimen 15 .…”
Section: Discussionmentioning
confidence: 99%
“…A mind map summarising the potential pitfalls 1–6,13,14 of the false‐negative Papanicolaou smear. The pitfalls described in the present study are grouped into categories…”
Section: Discussionmentioning
confidence: 99%
“…About half of these cases are diagnosed antenatally, and the other half around 12 months postpartum [5]. The incidence of abnormal cervical cytologic findings during pregnancy is 0.72 to 1.67% [10]. Most patients are diagnosed at an early stage of disease probably as the result of routine antenatal screening, but it may also be a possibility that advanced-stage disease interferes with conception [11].…”
Section: Introductionmentioning
confidence: 99%